Political engagement and government informing seeking: Increasing role of social media and mobile devices - Leon van Jaarsveldt (International Telecommunications Society (ITS), 2012)
Using OLS and binary logistic regression, in combination with the OSOR-model on a secondary dataset, the 2010-post election survey by Pew Internet and American Life project, this paper traces the direct paths of Facebook, Twitter, and mobile phone on online political participation and online political and government information seeking, as well as the indirect paths through wider view exposure and credibility. Findings provide support for the political use of Facebook and mobile phones as credible sources in both online political participation and online political information seeking, while not for Twitter. This suggests that Twitter is not seen as a platform for credible political engagement or information seeking or exposure to diverse views. By comparison, the path for Facebook through wider view exposure is also seen to lead to political participation and online political information through the path of credibility. This implies that any policy attempt to censor or control social media is a move in the wrong direction. There are also some implied findings for the need of an opinion leader.
Keywords: 330; Political participation; online political information seeking; Facebook; Twitter; mobile phones; wider view exposure; credibility; critical debate; opinion leader